2017
DOI: 10.1038/aps.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Protostemonine effectively attenuates lipopolysaccharide-induced acute lung injury in mice

Abstract: Protostemonine (PSN) is the main anti-inflammatory alkaloid extracted from the roots of Stemona sessilifolia (known as "Baibu" in traditional Chinese medicine). Here, we reported the inhibitory effects of PSN on lipopolysaccharide (LPS)-induced macrophage activation in vitro and LPS-induced acute lung injury in mice. Macrophage cell line RAW264.7 cells and mouse bone marrow-derived macrophages (BMDMs) were treated with PSN (1, 3, 10, 30 and 100 μmol/L) for 0.5 h and then challenged with LPS (0.1 μg/mL) for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The effects were shown to be associated with the decreased phosphorylation of MAP (mitogen-activated protein) kinase and proteinkinase B and the reduced expression of pro-inflammatory mediators. The results suggested that 137 may be a potential therapeutic agent in the treatment of acute lung injury (Wu et al 2018).…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects were shown to be associated with the decreased phosphorylation of MAP (mitogen-activated protein) kinase and proteinkinase B and the reduced expression of pro-inflammatory mediators. The results suggested that 137 may be a potential therapeutic agent in the treatment of acute lung injury (Wu et al 2018).…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…Following the first report on multidrug resistance properties of an ethanolic extract of Stemona aphylla (Limtrakul et al 2007), a series of studies evaluated the synergistic growth inhibitory effect of Stemona alkaloids with cancer chemotherapeutic agents (Chanmahasathien et al 2011a, b;Umsumarng et al 2013Umsumarng et al , 2015Umsumarng et al , 2017Umsumarng et al , 2018. Furthermore, their anti- inflammatory activity was investigated and regarded as an inhibition of the expression of diverse inflammatory mediators (Hosoya et al 2011;Lim et al 2015;Jung et al 2016;Lee et al 2016;Wu et al 2018). The present review also reports on the nematicidal activity (Huang et al 2016;Chen et al 2018) and other miscellaneous properties as well as on the pharmacokinetics of that class of alkaloids (Dong et al 2012;Sun et al 2012;Han et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“… Compounds Structure In vitro/in vivo Model (effective dose) Cells (effective concentration) Related pharmacological indicators Related molecular mechanisms Refs. Berberine 40 LPS/Cigarette smoke (10 mg/kg) 16HBE (10 μM) MPO↓ TNF-α↓ IL-6↓ IL8↓ KC↓ MIP-2↓ cPLA-2↓ MCP-1↓ Regulation of PERK‐mediated Nrf2/HO‐1 signaling pathway Inhibition of NF-κB signaling pathway [ [191] , [192] , [193] ] Tetrahydroberberrubine 41 LPS (10 mg/kg) THP-1 (10 μM) TNF-α↓ NO↓ Inactivation of MAPK, AKT and NF-κB signaling pathways [ 194 ] Cavidine 42 LPS (3 mg/kg) A549 (10 μg/mL) TNF-α↓ IL-6↓ Inhibition of NF-κB signaling pathway [ 195 ] Corynoline 43 LPS (15 mg/kg) MPO↓ TNF-α↓ IL-1β↓ IL-6↓ Up-regulation of Nrf2 signaling pathway Inactivation of NF-κB signaling pathway [ 196 ] Ukrain 44 I/R (70 mg/kg) TAS↓ TOS↓ OSI↓ None [ 197 ] Tetrahydhydrocoptisine 45 LPS (10 mg/kg) MPO↓ TNF-α↓ IL-6↓ Inhibition of NF-κB signaling pathway [ 198 ] Protostemonine 46 LPS (10 mg/kg) RAW264.7/BMDMs (30 μM) MPO↓ TNF-α↓ IL1-β↓ IL-6↓ iNOS↓ NO↓ Inactivation of MAPK and AKT signaling pathway [ 199 , ...…”
Section: Mechanisms Involved In Ali/ardsmentioning
confidence: 99%
“…This may be related to its inhibition of inflammatory responses via reducing expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, iNOS and NO) in RAW264.7, bone marrow-derived macrophages and ALI mice. Of note, the protective effects of protostemonine were related to inactivation of the MAPK and Akt signaling pathways [ 199 , 200 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…K63 polyubiquitination has an essential role in kinase activation in TLR pathways [20]. MAPKs are a superfamily composed of extracellular signal regulated kinase (ERK), c-jun N-terminal kinase (JNK), and p38 MAPK, which are critical in the regulation of inflammation and apoptosis [21,22]. With LPS stimulation, NF-κB is translocated from the cytoplasm to the nucleus and is activated to cause the transcription of pro-inflammatory genes [23].…”
Section: Introductionmentioning
confidence: 99%